2018
DOI: 10.1007/s12035-017-0839-1
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Improves Neurogenesis and Cognition in a Mouse Model of Alzheimer’s Disease

Abstract: The impairment of hippocampal neurogenesis at the early stages of Alzheimer’s disease (AD) is believed to support early cognitive decline. Converging studies sustain the idea that vitamin D might be linked to the pathophysiology of AD and to hippocampal neurogenesis. Nothing being known about the effects of vitamin D on hippocampal neurogenesis in AD, we assessed them in a mouse model of AD. In a previous study, we observed that dietary vitamin D supplementation in female AD-like mice reduced cognitive decline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(89 citation statements)
references
References 90 publications
3
84
2
Order By: Relevance
“…Deficits in adult neurogenesis may underlie the cognitive deficits in numerous neurological disorders such as depression (Sahay and Hen, 2007), Alzheimer's disease (Mu and Gage, 2011), Parkinson's disease (Marxreiter et al, 2013) and stroke (Dillen et al, 2019). Strategies that increase adult neurogenesis have been researched for their therapeutic potential to treat CNS disorders (Zhu et al, 2004;Yau et al, 2014;Hollands et al, 2016;Morello et al, 2018). Inhibition of H3R can protect against traumatic brain injury (TBI)-induced injury by improving neurogenesis (Liao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Deficits in adult neurogenesis may underlie the cognitive deficits in numerous neurological disorders such as depression (Sahay and Hen, 2007), Alzheimer's disease (Mu and Gage, 2011), Parkinson's disease (Marxreiter et al, 2013) and stroke (Dillen et al, 2019). Strategies that increase adult neurogenesis have been researched for their therapeutic potential to treat CNS disorders (Zhu et al, 2004;Yau et al, 2014;Hollands et al, 2016;Morello et al, 2018). Inhibition of H3R can protect against traumatic brain injury (TBI)-induced injury by improving neurogenesis (Liao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Dietary behavior, including caloric intake, meal frequency, meal texture, and meal content, has been reported to influence AHN [182]. The animal models showed that caloric restriction [183], hard-textured diet [184], and nutritional contents, such as polyunsaturated fatty acids (PUFA, such as omega-3 fatty acids) [185], polyphenols [186] (blueberries [187] and curcumin [188]), and vitamin D [189] positively regulate AHN and potentially restore behavioral impairment. Caloric restriction has neuroprotective roles in AD by increasing expression of neurogenesis-related genes and decreasing expression of inflammation-related genes in the PS1 and PS2 double knock-out mice [190].…”
Section: Potential Therapeutic Approaches Targeting Adult Neurogenesimentioning
confidence: 99%
“…In contrast to the missing clinical trials, several animal and cell culture studies underline a causal relationship between vitamin D and AD. One study described an increased neurogenesis and enhanced cognition after feeding a transgenic mouse model of AD (5xFAD mouse model) with a daily dose of 500 IU/kg vitamin D for 5 months [59]. Additionally, animal and cell culture studies allow analyzing combination therapies, for example, a supplementation of both vitamin D and resveratrol.…”
Section: Alzheimer's Diseasementioning
confidence: 99%